Penerapan Metode Menggambar Ilustrasi Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP Muhammadiyah 1 Alternatif Kota Magelang - Zakarya Zulfa, Muhammad; Tohirin, M.; Subur, Subur (Borobudur Islamic Education Review, 2026)
Islamic Religious Education (PAI) is not merely aimed at transferring religious knowledge but also at shaping reflective, critical, and responsible ways of thinking in everyday life. In practice, however, PAI learning at the junior high school level is still dominated by lecture and memorization methods, which provide limited opportunities for fostering students’ critical thinking skills. This study aims to describe the implementation of the drawing illustration method as an innovative approach to enhance students’ critical thinking in PAI subjects. The research employed a descriptive qualitative approach with eighth-grade students and a PAI teacher at SMP Muhammadiyah 1 Alternatif Kota Magelang as the subjects. Data were collected through direct classroom observation, interviews with teachers and students, documentation of students’ illustrations, and field notes. The results indicate that the implementation of the drawing illustration method consists of four stages: planning, implementation, results, and evaluation. The challenges encountered include limited time, variations in students’ drawing abilities, and a lack of supporting facilities. Nevertheless, this method proved effective as an alternative in PAI learning to foster students’ critical thinking in a contextual and creative manner.